ANALISIS KEBIJAKAN PENDIDIKAN DALAM PENYIAPAN SARANA DAN PRASARANA PADA PERENCANAAN PEMBELAJARAN TATAP MUKA DI SMA KRISTEN BARANA’ - Warya Awersendi S. Rumbiak; Witarsa Tambunan (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2021)
Covid 19 pandemic that occurred globally had an impact in the world of education to rethink about ways of school organization related to face-to-face learning preparation. The purpose of this paper is to analyze educational policies in the preparation of facilities and infrastructure as a strategy or effort to prepare face-to-face learning at Barana Christian Senior High School ', North Toraja district. This analysis uses a qualitative approach with descriptive research in which the data collection techniques are using school observations and literature review. The results of this study provide information to policy makers in schools in preparing appropriate facilities and infrastructure and planning face-to-face learning strategies that are effective and efficient, especially in the new normal era. The results of this study are expected to be researched further. Keywords: education policy analysis, facilities, face-to-face learning process